Foreign labor dynamics in Malaysia’s construction industry: Policy impacts and economic consequences - Saari, Mohd Nasir; Shuib, Md Shukri; Ajis, Mohd Na’eim bin (International Journal of Innovative Research and Scientific Studies, 2025)
The Malaysian construction sector’s reliance on foreign labor, especially in “3D” roles—dirty, dangerous, and difficult—has presented both economic advantages and socio-political challenges. This study investigates the impacts of Malaysia’s foreign worker policies on the construction industry, exploring dependency patterns, policy effectiveness, and implications for workforce localization. Utilizing a qualitative approach, the research incorporates in-depth interviews with policymakers, construction managers, and labor union representatives, supported by document analysis of policy records and labor statistics. Findings indicate that foreign workers comprise 70–80% of the workforce, driven by local reluctance towards lower-wage, physically demanding positions. The analysis reveals that inconsistent policy enforcement and the COVID-19 pandemic have destabilized labor supply, heightened employer concerns, and underscored the socio-economic risks of foreign worker dependency, including wage suppression and limited skill transfer to local workers. The study recommends a tiered levy system and workforce development incentives as strategic solutions to balance immediate labor demands with sustainable localization goals. By addressing workforce challenges and leveraging policy insights, this research contributes to the discourse on sustainable labor management in developing economies heavily reliant on foreign workers.